Allogeneic fibroblasts ameliorate intervertebral disc degeneration by reducing osteophytes in rabbits - Chen, Chen; Huang, Yizhuo; Shi, Lei; Zhou, Li; Zhou, Shenao; Wan, Hongjin; Yang, Xiao; Zhao, Jie (Frontiers in Medicine, 2024)
Introduction Low back pain (LBP) was commonly induced by intervertebral disc degeneration (IVDD), which is accompanied by the loss of disc height and osteophyte generation. Cell-based therapy is a promising treatment for preventing the degeneration of interverbral disc. In our study, allogeneic fibroblasts are shown to ameliorate intervertebral disc degeneration by reducing osteophytes in rabbits. Methods We established a rabbits-derived fibroblast (Rab-Fib) which could be expanded in vitro and constructed puncture-induced intervertebral disc degeneration rabbit model. Histologic and imaging examinations and analyses were performed after 2 weeks, 3 months, and 12 months. Results Our data indicate that stable and reliably-extracted allogeneic fibroblasts can effectively ameliorate intervertebral disc degeneration by reducing osteophytes. Conclusion Our study provides a basis for advancing the further translation of fibroblasts in intervertebral disc therapy.